Inhibition of Potassium Channels Affects the Ability of Pig Spermatozoa to Elicit Capacitation and Trigger the Acrosome Exocytosis Induced by Progesterone - Federico Noto (International Journal of Molecular Sciences, 2021)
During capacitation, sperm undergo a myriad of changes, including remodeling of plasma membrane, modification of sperm motility and kinematic parameters, membrane hyperpolarization, increase in intracellular calcium levels, and tyrosine phosphorylation of certain sperm proteins. While potassium channels have been reported to be crucial for capacitation of mouse and human sperm, their role in pigs has not been investigated. With this purpose, sperm samples from 15 boars were incubated in capacitation medium for 300 min with quinine, a general blocker of potassium channels (including voltage-gated potassium channels, calcium-activated potassium channels, and tandem pore domain potassium channels), and paxilline (PAX), a specific inhibitor of calcium-activated potassium channels. In all samples, acrosome exocytosis was induced after 240 min of incubation with progesterone. Plasma membrane and acrosome integrity, membrane lipid disorder, intracellular calcium levels, mitochondrial membrane potential, and total and progressive sperm motility were evaluated after 0, 120, and 240 min of incubation, and after 5, 30, and 60 min of progesterone addition. Although blocking potassium channels with quinine and PAX prevented sperm to elicit in vitro capacitation by impairing motility and mitochondrial function, as well as reducing intracellular calcium levels, the extent of that inhibition was larger with quinine than with PAX. Therefore, while our data support that calcium-activated potassium channels are essential for sperm capacitation in pigs, they also suggest that other potassium channels, such as the voltage-gated, tandem pore domain, and mitochondrial ATP-regulated ones, are involved in that process. Thus, further research is needed to elucidate the specific functions of these channels and the mechanisms underlying its regulation during sperm capacitation.